Socioeconomic status and retinoblastoma survival: Experience of a tertiary cancer center in Brazil. Issue 1 (22nd October 2020) - Mattosinho, Clarissa; Moura, Anna Tereza; Grigorovski, Nathalia; Araújo, Luiz Henrique; Ferman, Sima; Ribeiro, Karina
Abstract: Background: Little is known about socioeconomic status (SES) and its effects in childhood cancer survival. This study aims to discuss the association between SES and survival of patients with retinoblastoma (RB) from a tertiary treatment center. Procedure: A retrospective cohort study was conducted, including all patients with RB referred to the Brazilian National Institute of Cancer in Rio de Janeiro (January 2000‐December 2016). Results: Data from 160 patients were analyzed with mean age at diagnosis of 22.85 months (SD ± 14.29). Eighty‐three patients (51.9%) had an interval to diagnosis equal to or longer than six months, and 13 children (8.1%) abandoned treatment. Five‐year overall survival rate for all patients was 78.8% (95% CI, 72.4%‐85.9%). In a multivariate model, patients whose fathers had more than nine years of study had a lower death risk. Patients from families having more than one child under five years had a 213% higher risk of death compared with those living with no other small child. Treatment abandonment also had a profound effect on death risk. Conclusion: Childhood cancer is notably important considering the potential years of life lost. RB has even more important elements, as the possibility of vision loss in cases with delayed diagnosis. Family characteristics seem to be highly related to RB survival, especially in low‐ and middle‐income countries, where inequalities are still a public health issue. Strategies to improve survival should focus not only on large‐scale settings such as improving national healthcare systems but also on more personalized actions that might help to mitigate disparities.